Epistemologia em Ciência da Informação: uma análise à luz dos obstáculos bachelardianos - Santana, Sergio Rodrigues de (2023)
Science as a fruit of intelligence is instantiated by contemporary social and cultural phenomena conducted by passionate researcher and by sentient researcher. These interferences reflect in the domains of reason, philosophy and epistemology, and can potentiate epistemological obstacles, which are mental and material obstacles that impede the progress of science, this includes passion and love, among other feelings, emotions and affections that the information scientist directs to science itself from thinking and doing. Thus, the general objective is to investigate elements of Information Science that enhance epistemological obstacles, taking as references the historical and conceptual conditions that are intersectional and located between the identity approach and the epistemological approach. For that, we specifically sought to identify the epistemic discourses based on the field; build the epistemic networks of epistemological studies in the scientific production of the area; demarcate the technical phenomenon set within the scope of this production; delimit the epistemological obstacles; and describe the epistemological advances in the field of Information Science. The theoreticalmethodological framework focused on data triangulation through the Quadripolar Method, Discourse Analysis and the Network Analysis Method, based on a quantitative-qualitative approach. The work is guided by the historical-critical epistemology of Gaston Bachelard, operationalized from descriptions of events for the construction of an ideal of Information Science. There is conduction of criticism through suspensions, reconfigurations and disruptions as mental tools, thus conceived as critical and mental, since it focuses on the formation of the scientific spirit within the scope of the notion of Psychoanalysis of Scientific Knowledge and its theoretical extension. The locus of research was the Graduate Program in Information Science in Brazil, which includes 18 programs, with a time frame delimited in the period from 2000 to 2022. The corpus consisted of 132 works, of which 76 were dissertations, which corresponded to 58%, and 56 theses, which corresponded to 42% of the works analyzed. Of the 132 papers, a total of 274 'strata-essences' were extracted, which refer to the scientific discourses that enabled the construction of the micro-categories of analysis. These microcategories enabled the construction of macro-categories of analysis that refer to epistemological obstacles and epistemological advances. Those include Looping, Echo, Delay and Boomerang, while the latter include Postmodern Advancement, Social Advancement, Poly- Phenomenontechnical Advancement and Derivation of the Scientific Object. The systematized epistemic networks show the constructs that reflect the conformation of the field of Information Science, from the phenomenological techniques that portray both the obstacles and the epistemological advances. This phenomenotechnical set includes the lack of derivation, theoretical rumination, historicization, passionate unanimity, the unquestionable transfer of constructs, surveillance of the object, false return and comparison. It is considered that all these technophenomena configure, directly and indirectly, the search for the ideal construction of unity and/or identity in the field of Information Science.